A suffragist in the pages of “Kolce” – a Warsaw satirical and humorous magazine in the years 1871–1914 - Staniszewska, Aleksandra (Laughter, humour, satire, 2024)
The 19th-century world observed through the prism of satirical and humorous magazines was full of imperfections and hypocrisy. In such newspapers, absurdities in the moral and cultural sphere were criticized. The existing order was criticized and areas requiring changes were indicated. Although at the turn of the 19th and 20th centuries, the satirical and humorous press was not appreciated by the intellectual and artistic elite, its creators cannot be denied the perceptiveness and lightness of conveying information about the observed phenomena. Therefore, it is worth considering the satirical and humorous press as a very valuable source for research on the history of societies and culture, because it was the press that served the functions of agitation, moral and teaching, and at the same time, entertainment. The aim of the article is to present the image of women fighting for equal rights in the light of the weekly “Kolce”. This magazine, next to “Mucha”, boasted the largest readership, which resulted in a significant influence on public opinion. The pages of “Kolce” often referred to the women’s issue. Although the creators were aware of the need to change and re-discuss the position of women in the family and society, in accordance with the form of the magazine, they placed emphasis on presenting the incompetence of women. In the article, the author will try to answer the question – what features of appearance and character were attributed to emancipated women in the pages of “Kolce”? In conclusion, the author will consider whether showing the mockery of feminists and their activities could have had positive effects.